Β-hCG-induced mutant BRCA1 ignites drug resistance in susceptible breast tissue. (9th April 2019) - Sengodan, Satheesh Kumar; Hemalatha, Sreelatha K; Nadhan, Revathy; Somanathan, Thara; Mathew, Arun Peter; Chil, Arkadiusz; Kopczynski, Janusz; Nair, Rakesh Sathish; Kumar, Jerald Mahesh; Srinivas, Priya
Abstract: β-hCG expression in breast cancer is highly controversial with reports supporting both protective and tumorigenic effects. It has also been reported that risk of breast cancer at an early age is increased with full-term pregnancies if a woman is a BRCA1 mutation carrier. We have already demonstrated that BRCA1-defective cells express high levels of β-hCG and that when BRCA1 is restored, β-hCG level is reduced. Also, BRCA1 can bind to the promoter and reduce the levels of β-hCG. β-hCG induces tumorigenicity in BRCA1-defective cells by directly binding to TGFBRII and induces TGFBRII-mediated cell proliferation. In this study, we analyzed the mechanism of action of β-hCG on BRCA1 expression and its influence on drug sensitivity in breast cancer cells. We demonstrate that β-hCG induces mutant BRCA1 protein expression in BRCA1 mutant cells; however, in BRCA1 wild-type cells, β-hCG reduced wild-type BRCA1 protein expression. Transcriptionally, β-hCG could induce Slug/LSD1-mediated repression of wild-type and mutant BRCA1 messenger RNA levels. However, β-hCG induces HSP90-mediated stabilization of mutant BRCA1 and hence the overexpression of mutant BRCA1 protein, resulting in partial restoration of homologous recombination repair of damaged DNA. This contributes to drug resistance to HSP90 inhibitor 17AAG in BRCA1-defective cancer cells. A combination of HSP90 inhibitor and TGFBRII inhibitor has shown to sensitize β-hCG expressing BRCA1-defective breast cancers to cell death. Targeting the β-hCG–HSP90– TGFBRII axis could prove an effective treatment strategy for BRCA1-mutated breast tumors. Abstract : We demonstrate that β-hCG induces mutant BRCA1 protein expression which is stabilized by HSP90. This results tumor progression and drug resistance in BRCA1 mutated but not in BRCA1 wild type breast cancer cells.